Preoperative Hepatitis B seroprevalence and AntiHbs Levels in Children Consulted for Dental Procedures Under Anaesthesia - Fatma Kaya; Sadiye Sert (Genel Tıp Dergisi)
Background/Aims: Hepatitis B virus infection continues to be a major global and national public health concern. The aim of this study was to examine the seroprevalence of hepatitis B virus in children who were consulted to child health and diseases before dental intervention and to share our findings with the healthcare personnel involved on this subject. Methods: A total of 932 children were enrolled in the study, of which 533 (57.2%) were boys and 399 (42.8%) were girls. In the blood samples taken; hepatitis B virus tests were studied with the Enzyme Linked Immuno Sorbent Assay method. The results of blood samples and demographic data of the patients were evaluated. Results: HBsAg positivity was not found in any of the patients (0%). AntiHbs seropositivity was found in 73.8% of the whole patient population. No statistically significant difference was detected when comparing the anti-HBs levels based on gender. The average age of children with antiHbs seropositive was found to be statistically significant lower than that of those with antiHBs negative. The median anti-HBS antibody levels were significantly higher in the group of children under 5 years old than in the other two age groups older than five years old in our study. When investigating the association between the level of antiHBs and age, a weak negative correlation was found. Conclusions: Our study showed that the antiHbs seropositivity is higher in Konya compared to previous studies. It suggests that the national vaccination program has a positive impact on antiHbs seroprevalence. Our study revealed that children under the age of five displayed the highest levels of anti-HBs seropositivity, while the anti-HBs levels diminished with advancing age.